(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
In this article, a connection is established between the show “Ubu and the Truth Commission” and the historical context of Apartheid in South Africa. It stands out how the play critically approaches the events of that period, exploring themes related to truth, Injustice and oppression. In addition, it is discussed the original work of Alfred Jarry and his pataphysical philosophy, which serves as the basis for an aesthetics and for the theme chosen for the theatrical project mentioned.